Ergonomics study for workers at food production industry - Hamizatun, Mohd Fazi; N. M. Zuki, N. M.; M. F. F., Ab Rashid; A. N. M., Rose (EDP Sciences, 2016)
The health constraint faced by production workers affects the quality of the work. The productivity of the workers is affected by the Work-related Musculoskeletal Disorder (WMSD) which limits the movement of the workers. The comfort workplace condition, known as ergonomic environment is important to prevent the occurrence of the WMSD. Proper ergonomic workplace considers the condition of the workers while doing the assigned work. The objectives of this study are to identify the current problems related to ergonomic in food production process, to analyse the actual production data by using Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) and to recommend the ergonomic workplace environment based on the condition of the study. The study was done at a Small and Medium Enterprises (SME) food production company in the Klang Valley of Malaysia. The condition of the workers affects the productivity of the company due to workers’ health deficiency. From the findings, the workers are exposed to the awkward postures which leads to the Work-Musculoskeletal Disorders (WMSDs). Besides, the best height of the worker at the study area (critical area) to prevent the worker from WMSDs is within 155 cm to 160 cm. The results show that the workers are exposed to the WMSD in different level of risks which causes high absenteeism among the workers.